2015
DOI: 10.1007/s12043-015-1104-7
|View full text |Cite
|
Sign up to set email alerts
|

Isochronous Liénard-type nonlinear oscillators of arbitrary dimensions

Abstract: In this paper, we briefly present an overview of the recent developments made in identifying/generating systems of Liénard-type nonlinear oscillators exhibiting isochronous properties, including linear, quadratic and mixed cases and their higher-order generalizations. There exists several procedures/methods in the literature to identify/generate isochronous systems. The application of local as well as nonlocal transformations and -modified Hamiltonian method in identifying and generating systems exhibiting iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…But it remains an interesting curiosity to provide an explanation for why the analytic representations of both linear and nonlinear coupled system exhibit identical behavior. Moreover, one may also like to extend our method to construct Lagrangians for isochronous Liénard-type oscillators of different dimensions [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…But it remains an interesting curiosity to provide an explanation for why the analytic representations of both linear and nonlinear coupled system exhibit identical behavior. Moreover, one may also like to extend our method to construct Lagrangians for isochronous Liénard-type oscillators of different dimensions [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…One finds that certain Liénard type oscillators are solvable and also admit isochronous oscillations, whose frequencies are independent of their amplitudes [13]. Lie-group techniques, local and nonlocal transformations, etc., are employed to understand/generate new isochronous systems [14][15][16]. In another aspect, a systematic procedure has been developed to construct non-standard forms of Lagrangian/ Hamiltonian for specific nonlinear systems [17,18].…”
Section: Y T X F X Y T Y F X Y T X Y G X Y T X G X Y T Y H X Y T mentioning
confidence: 99%
“…It is observed that the nonlinear systems of the form (1), admitting eight parameter Lie point symmetry elements are linearizable under coordinate transformations if the functions g(x) and f (x) of equation (1) are related by the condition [16]…”
Section: Liénard Type-i Oscillators: Isochronous Oscillationsmentioning
confidence: 99%